Haploinsufficient tumor suppressor PRP4K is negatively regulated during epithelial‐to‐mesenchymal transition. Issue 11 (21st October 2021) - Clarke, Livia E.; Cook, Allyson; Mathavarajah, Sabateeshan; Bera, Amit; Salsman, Jayme; Habib, Elias; Van Iderstine, Carter; Bydoun, Moamen; Lewis, Stephen M.; Dellaire, Graham
Abstract: The pre‐mRNA processing factor 4 kinase (PRP4K, also known as PRPF4B) is an essential gene. However, reduced PRP4K expression is associated with aggressive breast and ovarian cancer phenotypes including taxane therapy resistance, increased cell migration and invasion in vitro, and cancer metastasis in mice. These results are consistent with PRP4K being a haploinsufficient tumor suppressor. Increased cell migration and invasion is associated with epithelial‐to‐mesenchymal transition (EMT), but how reduced PRP4K levels affect normal epithelial cell migration or EMT has not been studied. Depletion of PRP4K by small hairpin RNA (shRNA) in non‐transformed mammary epithelial cell lines (MCF10A, HMLE) reduced or had no effect on 2D migration in the scratch assay but resulted in greater invasive potential in 3D transwell assays. Depletion of PRP4K in mesenchymal triple‐negative breast cancer cells (MDA‐MB‐231) resulted in both enhanced 2D migration and 3D invasion, with 3D invasion correlated with higher fibronectin levels in both MDA‐MB‐231 and MCF10A cells and without changes in E‐cadherin. Induction of EMT in MCF10A cells, by treatment with WNT‐5a and TGF‐β1, or depletion of eukaryotic translation initiation factor 3e (eIF3e) by shRNA, resulted in significantly reduced PRP4K expression. Mechanistically, induction of EMT by WNT‐5a/TGF‐β1 reduced PRP4K transcript levels, whereas eIF3e depletion led to reduced PRP4K translation. Finally, reduced PRP4K levels after eIF3e depletion correlated with increased YAP activity and nuclear localization, both of which are reversed by overexpression of exogenous PRP4K. Thus, PRP4K is a haploinsufficient tumor suppressor negatively regulated by EMT, that when depleted in normal mammary cells can increase cell invasion without inducing full EMT.